COVID-19 and Emerging Markets : An Epidemiological Model with International Production Networks and Capital Flows - Cakmakli, Cem (IMF Working Papers; Working Paper, 2020)
We quantify the macroeconomic effects of COVID-19 for a small open economy by calibrating a SIR-multi-sector-macro model. We measure sectoral supply shocks utilizing teleworking and physical job proximity, and demand shocks with credit card purchases. Both shocks are also affected from changing infection rates under different lockdown scenarios. Being an open economy amplifies the economic costs through two main channels. First, the demand shock has domestic and external components. Second, the initial shock is magnified due to domestic and international input-output linkages.